2017
DOI: 10.1902/jop.2017.160815
|View full text |Cite
|
Sign up to set email alerts
|

A Sialidase‐Deficient Porphyromonas gingivalis Mutant Strain Induces Less Interleukin‐1β and Tumor Necrosis Factor‐α in Epi4 Cells Than W83 Strain Through Regulation of c‐Jun N‐Terminal Kinase Pathway

Abstract: A sialidase-deficient P. gingivalis mutant strain induces less IL-1β and TNF-α in epi4 cells than W83 strain through regulation of JNK pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…There are two possible reasons for this observation. The first reason might be that the lack of sialidase reduces the activity of important P. gingivalis virulence factors, such as fimbriae, LPS, capsule, and gingipains (Aruni et al, 2011 ; Li et al, 2012 , 2017 ). Virulence factors of P. gingivalis affect the interaction with macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are two possible reasons for this observation. The first reason might be that the lack of sialidase reduces the activity of important P. gingivalis virulence factors, such as fimbriae, LPS, capsule, and gingipains (Aruni et al, 2011 ; Li et al, 2012 , 2017 ). Virulence factors of P. gingivalis affect the interaction with macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The construction of ΔPG0352 and comΔPG0352 were as previously described (Li et al, 2017 ). Porphyromonas gingivalis W83, ΔPG0352 and comΔPG0352 were cultured on tryptic soy blood (TSB) agar plates supplemented with 5% sheep blood, 5% yeast extract, hemin (5 μg/ml) and 0.1% vitamin K under anaerobic conditions at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression levels of the genes, fimA , fimR , fimS , kgp , rgpA , and rgpB , in P. gingivalis were determined by real‐time PCR. P. gingivalis (10 7 CFU/mL) was treated with 1 mM DANA for 12 hours, then total RNA isolated, and quantitative real‐time PCR was performed as described previously 15 . Primer sequences are listed in Supplementary Table 1 in online Journal of Periodontology .…”
Section: Methodsmentioning
confidence: 99%
“…One particular enzyme that functions as a potential virulence factor is sialidase (neuraminidase) 13 . Our previous studies demonstrated that sialidase‐deficient mutants of P. gingivalis fail to produce an intact capsule, form less biofilm, have lower gingipain activity, cause rapid clearance by macrophages, and exhibit reduced virulence in a mouse abscess model 14‐17 . Therefore, suppression of sialidase using a sialidase inhibitor may be a potential method for alleviation of periodontitis.…”
Section: Introductionmentioning
confidence: 99%